An Algorithm for Determining Unloading Cycles in Dump Truck - Kozlowski, Tomasz; Michalak, Anna; Zimroz, Radoslaw; Sliwinski, Pawel; Kaniewski, Tomasz (IOP conference series. Earth and environmental science, 2019)
In copper ore deep mines of KGHM Polska Miedၺ S.A., the first stage of the transport department is to deliver the spoil to the screen. This stage is carried out by self-propelled mining machines. Transport can be done in two ways: by loaders or loaders cooperating with dump trucks. The amount of dump truck cycles during a single work shift can be used as indicators of a machine and operator performance evaluation. In order to increase the mining potential, it is necessary to continuously acquire and analyze information on work efficiency. The ability to synthesize the obtained data and case-study the relationship between them allows deepening knowledge of industrial processes and supports decision-making. Dump trucks used in the KGHM copper ore mines are equipped with a self-unloading mechanism. The paper describes a developed method and described an algorithm for segmenting signals coming from a dump truck with a self-unloading crate. The operation of the algorithm has been verified on data from a machine operated by several operators, taking into account various operational events.